In-Hospital Outcomes and Recurrence of Infectious Spondylitis in Patients with and without Chronic Hemodialysis: A Nationwide Cohort Study - Lu YA; Chen CY; Kuo G; Yen CL; Tian YC; Hsu HH (International Journal of General Medicine, 2022)
Yueh-An Lu, Chao-Yu Chen, George Kuo, Chieh-Li Yen, Ya-Chung Tian, Hsiang-Hao Hsu Department of Nephrology, Kidney Research Center, Linkou Chang Gung Memorial Hospital, Chang Gung University, College of Medicine, Taoyuan, TaiwanCorrespondence: Hsiang-Hao Hsu, Department of Nephrology, Kidney Research Center, Linkou Chang Gung Memorial Hospital, No. 5 Fu-Shin Street, Kweishan, Taoyuan, 333, Taiwan, Tel +886-3-328-1200 ext. 8181, Fax +886-3-3282173, Email hsianghao@gmail.comPurpose: The incidence of bloodstream infection among end-stage kidney disease (ESKD) patients on chronic hemodialysis (HD) was 26-fold higher than population controls, causing higher morbidity and costs. The aim of this investigation was to clarify the prognostic factors, in-hospital outcomes and recurrence of infectious spondylitis of patients with and without chronic HD.Patients and Methods: This nationwide study analyzed 2592 patients who admitted for first-time infectious spondylitis between January 1, 2003, and December 31, 2015. Patients were classified into the chronic HD or the non-HD group. The logistic regression model and the general linear model were utilized to determine the impact of chronic HD on in-hospital mortality and recurrence. The Cox proportional hazard model was used to estimate the predictive factors of in-hospital mortality and recurrence.Results: Compared to the non-HD group, patients in the chronic HD group had a higher risk of respiratory failure, sepsis, in-hospital mortality, longer hospital stay, and higher medical spending. Chronic HD was an independent risk factor for in-hospital mortality (hazard ratio 2.21, 95% confidence interval 1.34– 3.65, p=0.0019), but not for recurrence. Intravascular device implantation or revision was a prognosticator for the mortality of both groups and a predictor for recurrence of the non-HD group. Surgical treatment was associated with a decreased risk of recurrence, whereas treatment with CT-guided abscess drainage was associated with an increased risk of recurrence in both groups.Conclusion: Patients with infectious spondylitis who were receiving chronic HD had a higher in-hospital mortality compared to those without HD. Intravascular device implantations or revision within 6 months was a significant predictor of in-hospital mortality and disease recurrence. Surgical treatment of infectious spondylitis had a lower risk of recurrence than those with CT-guided abscess drainage in both patient groups.Keywords: infectious spondylitis, chronic hemodialysis, chronic kidney disease, end-stage kidney disease, outcome, recurrence, risk factor